Efeitos da gestão escolar e características individuais do diretor determinante do desempenho dos estudantes do Ensino Fundamental Brasileiro - Costa, Leandro Oliveira (2006)
By using the methodologies of Hierarchic Linear Models and Structural Models with Panel Data on the data of SAEB in 2001 and 2003, it was analyzed the effect of school management and the principal’s individual characteristics determinants to the students cognitive performance in the Brazilian primary schooling. When analyzing the individual characteristics of the students, it has been found similar results to national literature, that is, the socioeconomic conditions and the race are important factors to determine the performance in the examinations of proficiency in math. An interesting result is the best performance of the female students. This apparent contradiction may be related to what it was obtained for the schooling recurrence variable, since the majority of the repeater students are male. Among the twenty seven school variables, only eight of them diverged the results between the two models. The results obtained verified that the quality of the educators, teachers and principals, may be measured by their levels of schooling and experience in the school environment. Also signaling that the physical and pedagogical structure must be directed to the incentive the high frequency of the students and teachers, that is, well conserved and modernly equipped environments. The overall results indicate that the Brazilian schooling system needs financial resources to be applied to higher wages for teachers and principals, teachers more qualified, and a better structure that stimulates the students to go to school (as computers with access to the Internet) to improve the cognitive performance of the students.